Mitochondrial DNA in forensic use. Issue 3 (24th September 2021) - Syndercombe Court, Denise
Abstract : Genetic analysis of mitochondrial DNA (mtDNA) has always been a useful tool for forensic geneticists, mainly because of its ubiquitous presence in biological material, even in the absence of nuclear DNA. Sequencing, however, is not a skill that is part of the routine forensic analysis because of the relative rarity of requests, and the need for retention of necessary skill sets and associated accreditation issues. While standard Sanger sequencing may be relatively simple, many requests are made in the face of compromised biological samples. Newer technologies, provided through massively parallel sequencing (MPS), will increase the opportunity for scientists to include this tool in their routine, particularly for missing person investigations. MPS has also enabled a different approach to sequencing that can increase sensitivity in a more targeted approach. In these circumstances it is likely that only a laboratory that specialises in undertaking forensic mtDNA analysis will be able to take these difficult cases forward, more so because reviews of the literature have revealed significantly high levels of typing errors in publications reporting mtDNA sequences. The forensic community has set out important guidelines, not only in the practical aspects of analysis, but also in the interpretation of that sequence to ensure that accurate comparisons can be made. Analysis of low-level, compromised and ancient DNA is not easy, however, as contamination is extremely difficult to eliminate and circumstances leading to sequencing errors are all too easily introduced. These problems, and solutions, are discussed in the article in relation to several historic cases.